(untitled) (CIPEEX, 2022)
INTRODUCTION: ACCORDING TO MALAGUTTI AND KAKIHAR 2014, BURN INJURIES HAVE BEEN A MAJOR CAUSE OF MORBIDITY AND MORTALITY IN DEVELOPING COUNTRIES. IT CAN BE CAUSED BY THERMAL, ELECTRICAL, CHEMICAL OR RADIOACTIVE AGENTS, WHERE THE DEGREE OF IMPAIRMENT IS ASSESSED THROUGH THE DEPTH OF THE LESION. FROM THE ECONOMIC POINT OF VIEW THE TREATMENT OF THESE LESIONS ARE EXPENSIVE BECAUSE THEY ARE COMPLEX TREATMENTS THAT NEED SPECIFIC COVERINGS. THE TREATMENT OF BURN INVOLVES LOCAL AND SYSTEMIC EFFECTS, WHICH VARY ACCORDING TO THE DEPTH OF THE WOUND ITS LOCATION AND EXTENT. AS AN OPTION FOR LOCAL THERAPY, CURATIVES ARE USED THAT CONTAIN HEALING AND ANTI-INFECTIVE SUBSTANCES (TAVARES, SILVA, 2015). THE BURNED PATIENT REQUIRES A PROFESSIONAL NURSE TO ELABORATE CARE PLANS, TO HAVE A SUITABLE SCIENTIFIC KNOWLEDGE BASE, TECHNICAL SKILLS AND PERSONAL AND EMOTIONAL VALUES €‹€‹TO DEAL WITH THEIR SITUATION WITH COMPETENCE (TEIXEIRA; ALMEIDA, 2012). OBJECTIVE: THIS STUDY AIMED TO DISCUSS NURSING CARE AND POSSIBLE TREATMENTS IN RELATION TO BURN VICTIMS, THROUGH AN INTEGRATIVE REVIEW OF THE LITERATURE. METHODOLOGY: IT IS BASED ON AN INTEGRATIVE REVIEW OF THE LITERATURE, ARTICLES PUBLISHED IN THE VIRTUAL HEALTH LIBRARY (VHL), AVAILABLE IN FULL TEXTS, IN THE LATIN AMERICAN AND CARIBBEAN DATABASES ON HEALTH SCIENCES (LILACS) AND SCIENTIFIC ELETRONIC LIBRARY ONLINE (SCIELO), IN THE NURSING DATABASE (BDENF) AND ELECTRONIC JOURNAL OF THE BRAZILIAN SOCIETY OF BURNS (RBQ), FROM 2007 TO 2017, IN THE PORTUGUESE LANGUAGE. CONTENT ANALYSIS WAS USED TO ANALYZE THE DATA RESULT: RESULTS AND DISCUSSION OF THE DATA WERE OBTAINED THROUGH THE READING AND ANALYSIS OF ALL ARTICLES USED AND AFTER CATALOGING. THREE STAND OUT: 1) THE IMPORTANCE OF SYSTEMATIZATION OF ASSISTANCE IN THE TREATMENT OF VICTIMS OF BURNS; 2 EPIDEMIOLOGY AND ETIOLOGY; AND 3) TREATMENT OF THE BURN VICTIM. CONCLUSION: THE MAIN MORBIDITIES CAUSED BY THE BURN COME FROM THE PAIN AND SEQUELAE IT CAUSES. THE GOOD PROGNOSIS OF THE BURN VICTIM PATIENT IS INTERTWINED WITH THE APPROPRIATE TREATMENT AND AN EFFECTIVE NURSING SYSTEMATIZATION BASED ON TECHNICAL-SCIENTIFIC CARE. KEYWORDS: BURN INJURY, LOCAL TREATMENT, NURSING CARE